Islamic Brand Pada Era Revolusi Industri 5.0 - Kholishudin, Kholishudin; Rikantasari, Shelvyna (Studia Economica : Jurnal Ekonomi Islam, 2024)
This article discusses the phenomenon that is developing in society regarding Islamic brands in the era of the industrial revolution 5.0 which is currently developing. The labeling "Islamic" was used to attract economic development as well as compete for consumers in Indonesia. Islamic Brand here is not only used by brands in Indonesia but also used by foreign brands to label Islam on a product. Islamic branding is an important factor amidst the popularity of a product to determine its halalness. In business, religion can be used as a vehicle or medium to sell business products. This research uses a qualitative phenomenology type method to show that competition in business is getting tighter and wider. One of the competencies to boost is the religious factor as a tool to win business competition.  Namely, making the principles and values contained in religious teachings, such as halal labeling, become the basis and basis for doing business. Public perception of Islamic branding continues to increase as halal regulations are strengthened by the government. It is clear that the use of Islamic labeling is increasingly widespread in various business sectors. Because business actors feel the benefits of being able to boost sales and being able to compete to attract consumers